Machiavelli and instituent power - Albano Pina (International Journal of Philosophy and Social Values)
This article reconsiders the concept of instituent power from the perspective of Machiavelli’s republicanism. More specifically, it intends to see how the Florentine, while reflecting on the relation between society and institutions in Roman republic, already identifies the defining features of the mentioned power: namely, 1) his conflictual nature; 2) his inappropriability; 3) the fact that it consists in a continuous process, without beginning nor end. Additionally, I aim to ascertain what Machiavelli exactly understands by “institution” (in the nominal sense of the word). To this end, I will discuss the meaning and function of Roman “orders” (ordini) as described in his major work, Discourses on Livy. It is not my purpose, in the following, to present Machiavelli as a systematic theoretician of instituent power. I merely try, through an overview of the Discourses, to bring to light certain elements that intervene, or are implied, in such a concept, and that remain largely unthematized.